TEKNIK PENERJEMAHAN DALAM MENERJEMAHKAN TEKS RESEP MASAKAN - Supriatnoko; Almia Qudsyiah (EPIGRAM (e-journal), 2022)
The translation of recipe texts is classified as a special translation that is still less attractive to translators, even though recipe texts are much needed by culinary lovers, cooks, and Indonesia people who want to cook food or bake cakes, some of which are either already or not recognized in Indonesia. This particluar translation requires translators who are fluent in both languages as well as cooking techniques and local culture. The purpose of this study was to identify the translation techniques was to identify the translation techniques used by the author in translating written texts about recipes from Indonesian texts into English and from English texts into Indonesian. This research uses descriptive qualitative research method. Data collection techniques in this study using documentation techniques. Data were analyzed by qualitative descriptive analysis method. The results showed that from 18 translation techniques found 7 techniques used in translating recipe texts, namely adaptation techniques, amplification techniques, transposition techniques, reduction techniques, borrowing techniques, description techniques, and particularitation techniques. Among the translation techniques used, it can be concluded that adaptation techniques are widely used in translating recipe text: Sweet & Sour Sauce, Bakwan Tauge Udang, Lettuce Wrap, Dumling Bench.